2019
DOI: 10.5755/j01.eie.25.5.24358
|View full text |Cite
|
Sign up to set email alerts
|

Subclass Separation of White Blood Cell Images Using Convolutional Neural Network Models

Abstract: The white blood cells produced in the bone marrow and lymphoid tissue known as leucocytes are an important part of the immune system to protect the body against foreign invaders and infectious disease. These cells, which do not have color, have a few days or several weeks of life. A lot of clinic experience is required for a doctor to detect the amount of white blood cells in human blood and classify it. Thus, early and accurate diagnosis can be made in the formation of various disease types, including infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
0
31
1
1
Order By: Relevance
“…So, this can be used in further research studies to improve the success rate. The use of PCA along with CNN model did not provide good results [10].…”
Section: J Subclass Separation Of White Blood Cell Images Usingmentioning
confidence: 96%
“…So, this can be used in further research studies to improve the success rate. The use of PCA along with CNN model did not provide good results [10].…”
Section: J Subclass Separation Of White Blood Cell Images Usingmentioning
confidence: 96%
“…In this method, suitable shape and color features are extracted by means of the nucleus and the cytoplasm, yet there is no need for the cytoplasm to be segmented. The methods used in [19], [22], [23], [24], [25], and [26] are based on deep learning approaches. Therefore, their models are more complex and have more trainable parameters versus our classifier model which is SVM.…”
Section: Shape and Colormentioning
confidence: 99%
“…. There are some works that have utilized pre-trained CNNs for extracting features in the task of classifying WBCs [17,18,19,20]. In the task of diagnosing acute lymphoblastic leukemia, Rehman et al [17] compared the accuracy of using three different classifiers on the image features extracted by pre-trained CNNs.…”
Section: Introductionmentioning
confidence: 99%
“…A project also had demonstrated that Alexnet has the best performance as feature extraction for WBCs type classification in comparison with Lenet, and VGG16 architectures [14]. The Discrete Transform (DT), quadratic discriminant analysis (QDA), linear discriminant analysis (LDA), Support vector machine (SVM), k-nearest neighbors (kNN) with Alexnet also been compared to a softmax classifiers and the highest accuracy is the combination of QDA-Alexnet which is 97.78%.…”
Section: Related Workmentioning
confidence: 99%